2016
DOI: 10.1371/journal.pgen.1006260
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Variants for Cartilage Thickness and Hip Osteoarthritis

Abstract: Osteoarthritis is one of the most frequent and disabling diseases of the elderly. Only few genetic variants have been identified for osteoarthritis, which is partly due to large phenotype heterogeneity. To reduce heterogeneity, we here examined cartilage thickness, one of the structural components of joint health. We conducted a genome-wide association study of minimal joint space width (mJSW), a proxy for cartilage thickness, in a discovery set of 13,013 participants from five different cohorts and replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 49 publications
3
76
0
2
Order By: Relevance
“…We found a strong association with finger OA (p value=3.09*10 –08 , OR=1.25) and nominal significant association with severe hand OA (p value=2.80*10 –2 , OR=1.36), which has a low frequency in the population (online supplementary table S4). To see if rs4764133 also confers risk for other forms of OA, that is, OA of the hip and knee, we used the GWAS summary data of the treat OA consortium27 and the recently published minimal joint space width of the hip (mJSW) meta-analysis 18. No association was found between rs4764133 and hip or knee OA (online supplementary table S4).…”
Section: Resultsmentioning
confidence: 99%
“…We found a strong association with finger OA (p value=3.09*10 –08 , OR=1.25) and nominal significant association with severe hand OA (p value=2.80*10 –2 , OR=1.36), which has a low frequency in the population (online supplementary table S4). To see if rs4764133 also confers risk for other forms of OA, that is, OA of the hip and knee, we used the GWAS summary data of the treat OA consortium27 and the recently published minimal joint space width of the hip (mJSW) meta-analysis 18. No association was found between rs4764133 and hip or knee OA (online supplementary table S4).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated 18 novel OA risk loci that had been reported as being associated with the disease at a significance level close to or surpassing the genome‐wide threshold of P < 5 × 10 −8 (Table ). If the OA‐associated SNP was directly genotyped on an Illumina HumanOmniExpress array, we utilized those SNP data.…”
Section: Methodsmentioning
confidence: 99%
“…We had both methylation and genotype data available for a total of 87 patients who had undergone knee or hip joint arthroplasty (57 knee OA patients, 14 hip OA patients, and 16 patients who had undergone hip replacement due to a femoral neck fracture (Supplementary Table 1 OA loci investigation and mQTL analysis. We investigated 18 novel OA risk loci that had been reported as being associated with the disease at a significance level close to or surpassing the genome-wide threshold of P < 5 × 10 −8 (13)(14)(15)(16)(17)(18)(19)(20) ( Table 1). If the OA-associated SNP was directly genotyped on an Illumina HumanOmniExpress array, we utilized those SNP data.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies showed that common single variants in the DOT1L gene, with minor allele frequencies of 0.20–0.40, protect against osteoarthritis67. However, it is unknown how DOT1L affects this devastating disease.…”
mentioning
confidence: 99%